2019
DOI: 10.1128/mcb.00153-19
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Metabolic Flexibility in the Regulation of the DNA Damage Response by Nitric Oxide

Abstract: In this report, we show that nitric oxide suppresses DNA damage response (DDR) signaling in the pancreatic β-cell line INS 832/13 and rat islets by inhibiting intermediary metabolism. Nitric oxide is known to inhibit complex IV of the electron transport chain and aconitase of the Krebs cycle. Non-β cells compensate by increasing glycolytic metabolism to maintain ATP levels; however, β cells lack this metabolic flexibility, resulting in a nitric oxide-dependent decrease in ATP and NAD+. Like nitric oxide, mitoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 60 publications
(81 reference statements)
6
23
0
Order By: Relevance
“…β-cells lack this metabolic flexibility, as the coupling of glycolytic and mitochondrial oxidation of glucose is an essential regulatory feature of glucose-induced insulin secretion (26). A consequence of this lack of flexibility is the decrease in ATP levels in β-cells experiencing impaired mitochondrial oxidative capacity in response to nitric oxide (27,29) or inhibitors of mitochondrial respiration such as rotenone ( Figure 1E). In cells that maintain metabolic flexibility such as MEFs, the inhibition of mitochondrial respiration does not modify ATP levels ( Figure 1E), consistent with our previous observations (27).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…β-cells lack this metabolic flexibility, as the coupling of glycolytic and mitochondrial oxidation of glucose is an essential regulatory feature of glucose-induced insulin secretion (26). A consequence of this lack of flexibility is the decrease in ATP levels in β-cells experiencing impaired mitochondrial oxidative capacity in response to nitric oxide (27,29) or inhibitors of mitochondrial respiration such as rotenone ( Figure 1E). In cells that maintain metabolic flexibility such as MEFs, the inhibition of mitochondrial respiration does not modify ATP levels ( Figure 1E), consistent with our previous observations (27).…”
Section: Resultsmentioning
confidence: 99%
“…A consequence of this lack of flexibility is the decrease in ATP levels in β-cells experiencing impaired mitochondrial oxidative capacity in response to nitric oxide (27,29) or inhibitors of mitochondrial respiration such as rotenone ( Figure 1E). In cells that maintain metabolic flexibility such as MEFs, the inhibition of mitochondrial respiration does not modify ATP levels ( Figure 1E), consistent with our previous observations (27). These data correlate the β-cell selective inhibition of EMCV replication by mitochondrial respiratory chain inhibitors with decreases in ATP levels that are due to an inability of b-cells to compensate for the inhibition of mitochondrial oxidative metabolism with increases in glycolytic flux (27).…”
Section: Resultsmentioning
confidence: 99%
“…Nitric oxide mediates the inhibitory actions of cytokines on insulin secretion ( 23 , 24 , 25 ) by attenuating the Krebs cycle enzyme aconitase and complex IV of the electron transport chain ( 26 , 27 ). Because of the coupling of aerobic and anaerobic metabolisms, β-cell ATP levels are decreased when mitochondrial respiration is inhibited because of a lack of glycolytic compensation ( 17 , 28 , 29 , 30 , 31 ). In non–β-cells, nitric oxide does not decrease ATP because they have the metabolic flexibility to increase glycolysis ( 28 ).…”
mentioning
confidence: 99%
“…Because of the coupling of aerobic and anaerobic metabolisms, β-cell ATP levels are decreased when mitochondrial respiration is inhibited because of a lack of glycolytic compensation ( 17 , 28 , 29 , 30 , 31 ). In non–β-cells, nitric oxide does not decrease ATP because they have the metabolic flexibility to increase glycolysis ( 28 ). Recently, we have shown that the same metabolic pathways responsible for the control of glucose-stimulated insulin secretion are inhibited by nitric oxide, and this results in an attenuation in ATM signaling and the inhibition of DNA damage–induced β-cell apoptosis ( 14 , 28 , 32 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation